HUBUNGAN PENGETAHUAN DENGAN SIKAP PENCEGAHAN TERHADAP HIV/AIDS PADA REMAJA PEREMPUAN DI SMA NEGERI 1 OKU - Siti Yuriah; Ramayani Ramayani; Willy Astriana (Jurnal Kesehatan Abdurrahman, 2026)
Human Immunodeficiency Virus is a virus that attacks the human immune system. Meanwhile, Acquired Immunodeficiency Syndrome is a collection of symptoms of a disease that results in a decline in the immune system. Based on data reported by the Ministry of Health, HIV/AIDS cases in Indonesia were recorded as many as 36,902 people infected with HIV/AIDS in January-December 2021. The number of HIV/AIDS cases in Indonesia from 2011 to 2021 continues to fluctuate, with the largest number of HIV cases occurring in 2019, namely 50,282 people, and the largest number of AIDS cases occurring in 2013, namely 12,214 people. Despite continuing to fluctuate, Indonesia itself is estimated to have 21% of the 5,701 reported HIV/AIDS cases in women. The purpose of this study was to determine the relationship between knowledge and attitudes of adolescent girls towards HIV/AIDS prevention and transmission at SMA Negeri 1 OKU. The research method used quantitative, which is an analytical survey with a cross-sectional approach. The research sample of 55 was taken by purposive sampling. The research location was at SMA Negeri 1 OKU. The results of the Kendall Tau analysis showed that the p value was 0.000 or p value <0.05, which means there is a significant relationship between knowledge and attitudes about HIV/AIDS prevention in female adolescents at SMA Negeri 1 OKU. The results of the correlation coefficient value of 0.096 in this test indicate that there is a very low closeness relationship. It is hoped that schools or health workers will provide counseling about HIV/AIDS to female students at SMA Negeri 1 OKU so that female students have knowledge so they can prevent or avoid HIV/AIDS and other infectious diseases.